Corrosion Assessment of Materials for a Chemical Looping Combustion Air Reactor Used for Carbon Capture and Storage - Ataia, Mohammad; Fuhrman, David (My University, 2025)
Chemical Looping Combustion (CLC) with Carbon Capture and Storage (CCS) has shown promising advancement regarding carbon negative emissions. To increase the electrical efficiency of CLC, optimized corrosion resistance of the superheaters is crucial. This study focused on the air reactor (AR) of the CLC system at 600 °C and its potential corrosion hot spots at the superheaters. Six different alloys were tested in a clean and an alkali slip (0.5 ppm KOH) laboratory environment. Through gravimetric measurements and scanning electron microscope micrographs, the results showed that the Ni-based alloys and the ferritic FeCrAl alloys performed best from a corrosion point of view. Ferritic steels and austenitic stainless steels strengthened the issue by showing poorer gravimetric and micrographic results.